Sacred Bodies: Materiality and Corporeality in Early Reformation Disputes - Ptaszyński, Maciej (Reformation, 2025)
This article examines the 1525 vandalization and looting of the churches in Stralsund, in modern northeast Germany, focusing on the destruction of sacred objects and its implications for religious and social change. Through Catholic and Protestant testimonies, the study reveals how bodily and material practices influenced the conflict, highlighting the role of religious objects, property disputes, and violence against the clergy. By framing these events within the evolving Lutheran identity, the article reinterprets the Stralsund events as both a religious and a sociopolitical struggle. This analysis contributes to an understanding of the Reformation's impact on sacral materiality and the embodiment of faith practices.